Putting a face with a name: avatars, relationship marketing and service failure/recovery. (16th November 2010) - Taylor, David G.
As the internet environment becomes more competitive, firms seek new ways to attract, retain and manage online customers. With the increasing popularity of social networking sites, some marketers are attempting to add a social dimension through the use of avatars – graphic representations of humans that can be animated or serve as virtual spokespeople. Several studies have suggested that avatars increase flow, arousal, hedonic and utilitarian value, satisfaction, purchase intention. Two exploratory experiments extend this research by studying the effect of avatars on consumers' relationship intentions and the impact of service failure. The results suggest that avatars increase perceived communication and perceived relationship benefits, leading to increased relationship marketing success. In addition, customer loyalty is higher when avatars are present, even after a service failure.